VALIDITAS DAN PRAKTIKALITAS HYPOTHETICAL LEARNING TRAJECTORY (HLT) TOPIK INTEGRAL BERBASIS RME BERBANTUAN GEOGEBRA - Kelly Angelly Hevardani (Departemen Matematika, 2021)
Based on the results of preliminary research, it was found that integral learning tended to use existing textbooks and there was no use of technology in teaching materials. This study aimed to developing instructional design with RME assisted by GeoGebra on topic integral. This study that was combined Plomp and Gravemeijer & Cobb models, which consisted of three phases, namely preliminary research, development or prototyping phase, and assessment phase. The learning design in question is HLT which is implemented on student worksheets. This HLT consists of three components, namely the learning objectives, a series of student activities, and predictions of student answers and anticipations that must be done by the teacher. The subjects of this study were students of class XI SMAN 8 Padang. The data collection instrument used were interview sheets, observation sheets, questionnaires, and test on mathematical reasoning abilities. The results showed that the intructional design based on RME assisted by GeoGebra, especially topic integral can be said to be valid and practical.Keywords-RME, Integral, GeoGebra, HLT